Carbon export efficiency and phytoplankton community composition in the Atlantic sector of the Arctic Ocean. Issue 6 (1st June 2015) - Le Moigne, Frédéric A. C.; Poulton, Alex J.; Henson, Stephanie A.; Daniels, Chris J.; Fragoso, Glaucia M.; Mitchell, Elaine; Richier, Sophie; Russell, Benjamin C.; Smith, Helen E. K.; Tarling, Geraint A.; Young, Jeremy R.; Zubkov, Mike
Abstract: Arctic primary production is sensitive to reductions in sea ice cover, and will likely increase into the future. Whether this increased primary production (PP) will translate into increased export of particulate organic carbon (POC) is currently unclear. Here we report on the POC export efficiency during summer 2012 in the Atlantic sector of the Arctic Ocean. We coupled 234‐thorium based estimates of the export flux of POC to onboard incubation‐based estimates of PP. Export efficiency (defined as the fraction of PP that is exported below 100 m depth: ThE ‐ratio) showed large variability (0.09 ± 0.19–1.3 ± 0.3). The highest ThE ‐ratio (1.3 ± 0.3) was recorded in a mono‐specific bloom of Phaeocystis pouchetii located in the ice edge. Blooming diatom dominated areas also had high ThE ‐ratios (0.1 ± 0.1–0.5 ± 0.2), while mixed and/or prebloom communities showed lower ThE ‐ratios (0.10 ± 0.03–0.19 ± 0.05). Furthermore, using oxygen saturation, bacterial abundance, bacterial production, and zooplankton oxygen demand, we also investigated spatial variability in the degree to which this sinking material may be remineralized in the upper mesopelagic (<300 m). Our results suggest that blooming diatoms and P. pouchetii can export a significant fraction of their biomass below the surface layer (100 m) in the open Arctic Ocean. Also, we show evidence that the material sinking from a P. pouchetii bloom may be remineralized (>100 m) at a similar rate as the material sinking from diatom blooms in the upper mesopelagic, contrary to previous findings. Key Points: Arctic export efficiency displays large variability Blooming diatoms and Phaeocystis sp. have the highest export efficiency More work is needed on upper mesopelagic remineralization in the Arctic